Keynesian Economics and Price Theory: Re-orientation of a Theory of Monetary Economy - Otaki, Masayuki (Springer, 2015)
This book reconstructs Keynesian macroeconomics so that it is compatible with the neoclassical dynamic microeconomic theory. This theory adopts three postulates: rational expectations, perfect price flexibility, and exclusion of the money in utility function (MIU). Based on the new theoretical finding that the Lucas model (1972) contains multiple equilibria, the author unifies Keynesian and monetarist theories within the same framework. The book applies the above basic theory to international macroeconomics and economic growth theory.